Angular analysis of the B+ →K*+ μ+ μ− decay - Aaij, Roel; Neubert, Sebastian; Sarpis, Mindaugas; Schmelling, Michael; Stemmle, Simon; Unverzagt, Daniel Joachim; Uwer, Ulrich; Waldi, Roland; Wang, Chishuai; Witola, Lukas; Zhelezov, Alexey (Physical review letters, 2021)
We present an angular analysis of the B+→K*+(→K0Sπ+)μ+μ− decay using 9 fb−1 of pp collision data collected with the LHCb experiment. For the first time, the full set of CP-averaged angular observables is measured in intervals of the dimuon invariant mass squared. Local deviations from standard model predictions are observed, similar to those in previous LHCb analyses of the isospin-partner B0→K*0μ+μ− decay. The global tension is dependent on which effective couplings are considered and on the choice of theory nuisance parameters.